STRATEGI YOUTUBER BENGKULU DALAM MENGELOLA KONTEN UNTUK MENDAPATKAN PENGHASILAN (Studi Pada Akun Youtube Channel Muhammad Rizki) - Kamilah Astari (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
The purpose of this study is to find out the Bengkulu YouTuber's strategy in managing content to earn income and to find out the source of a YouTuber's income. This study uses a descriptive qualitative approach. The method of data collection was done through observation, in-depth interviews and documentation. The subject of this research is Muhammad Rizki who is a Bengkulu YouTuber. The validity of research data using triangulation technique. The results show that: a YouTuber has a certain strategy to earn income. The income of a YouTuber is obtained through various sources. In managing content, Rizki faced various challenges, lack of enthusiasm to build a YouTube Channel, being suspended from YouTube and the company.